A much lower density for the transiting extrasolar planet WASP-7 - Southworth, John; Dominik, M.; Jørgensen, U. G.; Rahvar, S.; Snodgrass, C.; Alsubai, K.; Bozza, V.; Browne, P.; Burgdorf, M.; Novati, S. Calchi; Dodds, P.; Dreizler, S.; et al. (Astronomy and astrophysics, 2011)
We present the first high-precision photometry of the transiting extrasolar planetary system WASP-7, obtained using telescope defocussing techniques and reaching a scatter of 0.68 mmag per point. We find that the transit depth is greater and that the host star is more evolved than previously thought. The planet has a significantly larger radius (1.330 ± 0.093 RJup versus $\er{0.915}{0.046}{0.040}$ 0.91 5 -0.040 + 0.046 RJup) and much lower density (0.41 ± 0.10 ρJup versus $\er{1.26}{0.25}{0.21}$ 1.2 6 -0.21 + 0.25 ρJup) and surface gravity (13.4 ± 2.6 m s-2 versus $\er{26.4}{4.4}{4.0}$ 26. 4 -4.0 + 4.4 m s-2) than previous measurements showed. Based on the revised properties it is no longer an outlier in planetary mass-radius and period-gravity diagrams. We also obtain a more precise transit ephemeris for the WASP-7 system.
Gesehen am 19.10.2022